Indigenist Visual Discourse: Martín Chambi Legacy and its Metrics in the Digital Space - Yucra-Mamani, Yudi Janeh; Aragón-Cruz, Walker Ernesto; Torres-Cruz, Fred (VISUAL REVIEW. International Visual Culture Review / Revista Internacional de Cultura Visual, 2025)
This study analyzes the indigenist visual discourse of Martín Chambi legacy and its metrics in the digital space, using a mixed-methods approach that combines qualitative and quantitative techniques. The research, which is descriptive and employs a non-experimental cross-sectional design, utilizes metric analysis and visual content analysis. The results show that Chambi visual discourse remains relevant in the digital era, adapting to the interaction dynamics of platforms such as Facebook, TikTok, Instagram, and YouTube. Attention metrics, such as reactions, comments, and shares, reflect sustained interest in his work. It is concluded that his legacy is not only preserved but also transformed and amplified through digital interactions, solidifying his status as a visual reference of the Andean world.